Acquired hemoglobin H disease in a patient with aplastic anemia evolving into acute myeloid leukemia - Figueiredo, Maria Stella; Vicari, Perla; Kimura, Eliza Yuriko Sugano; Antunes, Sandra Vallin; Yamamoto, Mihoko (São Paulo Medical Journal, 2004)
CONTEXT: The prognosis of severe aplastic anemia has improved since the introduction of bone marrow transplantation and treatment with antithymocyte globulin. In contrast to the success of these protocols, studies with long term follow-up have shown the occurrence of clonal diseases such as paroxysmal nocturnal hemoglobinuria, myelodysplastic syndrome and acute leukemia in aplastic anemia. CASE REPORT: We report the first case of a Brazilian patient with aplastic anemia who developed myelodysplastic syndrome and acute myeloid leukemia showing acquired hemoglobin H and increased fetal hemoglobin.